A Study on Selected Indian Fiction and Discourse of Resistance: Exploring Themes of Resistance in Indian Fiction (Journal of Advances and Scholarly Researches in Allied Education, 2013)
This research project aims to study the discourse ofresistance in selected Indian fiction. The focus is specifically on resistancearticulated in terms of caste, class, gender and postcoloniality. The fictionselected for the purpose includes Laxman Gaikwad’s The Branded (Marathi,1987), Arundhati Roy’s The God of Small Things (English, 1997), AmitavGhosh’s The Hungry Tide (English, 2004), P.